Development Accounting Rule disclosure by accounting policies in the light of Islamic and electronic banking Activities (Proposal pattern): Proposal pattern (Journal of Accounting and Financial Studies ( JAFS ), 2016)
the bank sect for any country  is very important  because  its represent a major  nerve   to feed a verity economic and finance activities .development any state measure by development  banking  sets and its represent  important  factor to investors attract . and because  important  of this subject ,teen accounting rule is a specialized for it .its related by  Disclosures in the Financial Statements Of Banks and The Similar Institutions, its accredit  by auditing and accounting standard  consul in republic of Iraq.in date 10/28/1998.                                                    This rule not adjusted since that time to contain the development and  a variables it witnessed  this sect for example Islamic and electronic banking Activities witch is speared in Iraq. So that suggested this research some a necessary  adjustment  for this rule to become more effective  Accounting disclosure enhancement in the banking  Activities